2009
DOI: 10.1128/jcm.00925-08
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Phage-Associated Virulence Genes in Pharyngeal Group A Streptococcal Strains Isolated in Italy

Abstract: The presence and assortment of 16 known virulence/resistance genetic determinants carried by prophages or prophage-like elements were tested in 212 clinical group A Streptococcus (GAS) strains and related to available data from SmaI macrorestriction/pulsed-field gel electrophoresis analysis and emm typing. A strong correlation existed among the three analyses. This finding supports the substantial contribution to the evolution and diversification of the GAS genome attributed to phages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
(29 reference statements)
0
7
0
Order By: Relevance
“…46,47 Studies suggest the M type distributions of many resistance traits are not well conserved over time and space. 22,34,36,[46][47][48] However, a recent US study showed that even these highly variable traits segregate significantly with M type over shorter periods of time. 44 Macrolide resistance offers an excellent example of a phenotype that is more highly correlated with M type and for which M typing offers a significant degree of predictive power.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
See 2 more Smart Citations
“…46,47 Studies suggest the M type distributions of many resistance traits are not well conserved over time and space. 22,34,36,[46][47][48] However, a recent US study showed that even these highly variable traits segregate significantly with M type over shorter periods of time. 44 Macrolide resistance offers an excellent example of a phenotype that is more highly correlated with M type and for which M typing offers a significant degree of predictive power.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…4,[12][13][14]20,72 The genes mobilized by these elements include pyrogenic superantigens (speA and speC), DNases, phospholipase A2 (similar to snake venom toxin), mefA (a macrolide efflux factor) and many others. 4,12,48 Many of these have been associated with specific phenotypes, but none have proven to be solely responsible for, or uniquely associated with, specific symptoms, sequelae or outcomes. 10,12 It is possible that these virulence factors act in groups to produce specific effects on hosts and their effects may be modulated by the M protein with which they are associated, as the M protein is clearly a critical virulence factor itself.…”
Section: Gas Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also in the case of ⌽m46.1, its ability to lysogenize seems to be not influenced by the strain emm type. The confirmed low M-type specificity might be one explanation for the wide diffusion of ⌽m46.1 in GAS strains showing various emm types (20). An exception is represented by the strains belonging to emm77, emm78, and emm89.…”
Section: Mef(a)-tet(o)-negative Strains Into Mef(a)-tet(o)-positivementioning
confidence: 80%
“…Even with the wide range of emm types seen in this study, this finding still leaves the possibility that the emm serotype may be playing a role in the differences in gene expression seen within this study. Supporting this rationale is the high number of phagerelated genes expressed in one cluster and the known variability of prophages among emm types (Vitali et al, 2009). However, phage-associated genes only accounted for a portion of the differences in gene expression between the two clusters.…”
Section: Discussionmentioning
confidence: 99%